Chapters of the Izbornik of Bulgarian Tsar Simeon in the Saratov Edition of the Zlatostruy - Čistiakova, Marina (Slavistica Vilnensis, 2022)
The present article covers the results of a study on the source texts of the Saratov edition of the Zlatostruy (Crysorrhoas) сollection, known in a single copy that dates back to the end of the 15th century (Sar. 45). The manuscript contains 127 chapters, with the first 78 of them deriving from readings of the Zlatostruy. The remaining chapters of the Saratov edition of the Zlatostruy were compiled from fragments of other collections of teachings. One of them was the Izbornik (Florilegium), compiled for Tsar Simeon during the First Bulgarian Empire. The Izbornik is one of the most important sources on the history of translated Slavonic literature. Excerpts from Simeon’s Izbornik are included in 8 chapters of the Saratov edition of the Zlatostruy (ch. 92, 99, 112, and 114‒118). Comparative analysis has demonstrated that a copy of the comprehensive edition of the source was used by the scribes. Three chapters of the Sar. 45 fully derive from Simeon’s Izbornik (ch. 115, 117, 118). In five cases, borrowings from this source are combined with passages from other collections of teachings (ch. 92, 99, 112, 114, and 116). In the process of borrowing, the scribes would copy chapters of the Izbornik in their order of precedence, combine passages from different fragments of the source text, or extract some passages from the source text. Borrowings from the Florilegium of Bulgarian Tsar Simeon in the Sar. 45 underwent editorial changes: the source text was shortened and some words were substituted by others.
Keywords: Church Slavonic manuscript heritage; textual criticism; sources of sermons; Zlatostruy (Crysorrhoas); Saratov edition; Izbornik of Tsar Simeon